PSIKOLOGI HUKUM DALAM PENDIDIKAN: SEBUAH KAJIAN LITERASI - Airell, Ansgarius (Gapenas Publisher, 2023)
This article discusses the role of legal psychology in an educational context with a focus on legal literacy. Legal psychology is a branch of psychology that examines the interaction between law and individuals and the systematization of legal knowledge in a psychological context. Legal literacy becomes important in education to equip individuals with an adequate understanding of the law in everyday life. Through a literature review, this article outlines how legal psychology can be applied in education to improve students' legal literacy. The practical implications of the integration of legal psychology in the educational curriculum are also discussed. In conclusion, this article highlights the importance of understanding the role of legal psychology in improving legal literacy among students as an effort to create a more law-aware society